Implementation of E-Sister Management Information System in Improving the Quality of Educators - Ahmad Zainullah; Ainol Ainol; Ismatul Izzah (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Educational institutions currently have various needs in implementing and managing their organizational organizations. One of the needs of educational institutions is the provision of access to data and information obtained from the process of collecting, recording, managing, duplicating, storing and sending until the information is received by decision makers. In accordance with the 1945 Constitution ARTICLE 28C, the first paragraph which reads, every person has the right to develop himself through meeting his basic needs, has the right to receive education and to benefit from science and technology, arts and culture, in order to improve his quality of life and for the welfare of mankind, but these activities if done manually it will be less effective because of the tendency of the current human mindset to want everything fast and easy so that it can be completed on time in the process and provide maximum output of course the management information system is a part of management science starting from planning, organizing, leadership and control to achieve successful activities in a research organization. This research was conducted at SMA Unggulan Hafsa Zainul Hasan BPPT Genggong Probolinggo that the institution has used a management information system (electronic integrated system) in order to respond to all changes and developments, especially in the field of education, both in the process of teaching and learning activities or, in employee administration services. The management information system in the field of education was developed to meet the needs of madrasa/school institutions, Haf-sa Zainul Hasan Superior High School BPPT Ganggong Probolinggo as one of the leading labeled Islamic education institutions is an institution that always maintains service quality by implementing the latest IT technology utilizing information systems management based on E-SISTER in providing educational services to consumers. The services provided are not only related to academics, such as online learning, integrated presence with whatsae-sisters of student guardians, but also non-academic services such as administration and others